The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1667/rr13887.1
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Proton Irradiation Causes Long-Term Damage to Hematopoietic Stem Cells in Mice

Abstract: Space flight poses certain health risks to astronauts, including exposure to space radiation, with protons accounting for more than 80% of deep-space radiation. Proton radiation is also now being used with increasing frequency in the clinical setting to treat cancer. For these reasons, there is an urgent need to better understand the biological effects of proton radiation on the body. Such improved understanding could also lead to more accurate assessment of the potential health risks of proton radiation, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 40 publications
6
42
0
Order By: Relevance
“…We observed depletion of HSCs 3 months after exposure, as well as decreased repopulation capacity of the remaining stem cells in a competitive transplant assay. Previously, elevated levels of reactive oxygen species correlating with decreased HSCs have been observed at 22 weeks after exposure to proton radiation, in line with our observations here . Added mutational load, which is known to occur with MMR defects and radiation exposure , however, did not exacerbate the latent phenotype, at least regarding HSC function.…”
Section: Discussionsupporting
confidence: 92%
“…We observed depletion of HSCs 3 months after exposure, as well as decreased repopulation capacity of the remaining stem cells in a competitive transplant assay. Previously, elevated levels of reactive oxygen species correlating with decreased HSCs have been observed at 22 weeks after exposure to proton radiation, in line with our observations here . Added mutational load, which is known to occur with MMR defects and radiation exposure , however, did not exacerbate the latent phenotype, at least regarding HSC function.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, their results showed that inhibition of NOX4 can protect mice similar to a potent radioprotector (N-acetyl cysteine) [19,20]. Other studies confirmed that continuous ROS production through stimulation of redox interactions plays a key role in the development of both early and late effect of IR [21][22][23]. Weyemi et al showed that inactivation of both NOX4 and NOX5 can mitigate ROS production and oxidative DNA damage in irradiated human fibroblast cells [24].…”
Section: Molecular Mechanisms For Continuous Ros Production Followingmentioning
confidence: 98%
“…However, after exposure to high doses of ionizing radiation, cells may undergo massive chromosome damage, depending on cell type . Cells with high mitotic activities may undergo higher levels of DNA damage and cell death, while those with low mitosis activities, have a longer time to repair damaged DNA and show a low incidence of cell death . The production of reactive oxygen species (ROS) by ionizing radiation is responsible for two‐thirds of DNA damage immediately after exposure.…”
Section: Radiation‐induced Injury In Normal Tissuesmentioning
confidence: 99%
“…2,16 Cells with high mitotic activities may undergo higher levels of DNA damage and cell death, while those with low mitosis activities, have a longer time to repair damaged DNA and show a low incidence of cell death. [17][18][19][20] The production of reactive oxygen species (ROS) by ionizing radiation is responsible for two-thirds of DNA damage immediately after exposure. However, studies have revealed that high doses of ionizing radiation may stimulate chronic oxidative stress because of endogenous production of ROS and nitric oxide (NO) by macrophages, lymphocytes, as well as some pro-oxidants, such as nicotinamide adenine dinucleotide phosphate oxidase in other cells.…”
Section: Injury In Normal Tissuesmentioning
confidence: 99%